2012
DOI: 10.4236/jbpc.2012.34039
|View full text |Cite
|
Sign up to set email alerts
|

Microwave based reversible unfolding and refolding of alcohol oxidase protein probed by fluorescence and circular dichroism spectroscopy

Abstract: The reversible effect of microwave mediated denaturation of protein at low exposure time of 10 s has been demonstrated for the first time. The effect of microwave (2.45 GHz and 900 W) was confirmed in a homo-octameric alcohol oxidase in aqueous solution of pH 7.5. The unfolding events did not transverse through any intermediate states and no subunits of the protein were detached during the process. The refolding of the protein achieved at 4˚C for 24 h had regenerated the native enzyme. This reversible refoldin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…23,24 Studies of the influence of microwave irradiation on the hydration of various solutes might have practical implications for biology. It has been reported that microwave irradiation enhances the folding and unfolding kinetics of globular proteins, [25][26][27] as well as protein aggregation through alteration of the protein conformation. 28 Several studies suggest that microwaves induce structural rearrangements of proteins not related to the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Studies of the influence of microwave irradiation on the hydration of various solutes might have practical implications for biology. It has been reported that microwave irradiation enhances the folding and unfolding kinetics of globular proteins, [25][26][27] as well as protein aggregation through alteration of the protein conformation. 28 Several studies suggest that microwaves induce structural rearrangements of proteins not related to the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Before heating treatment, compared to the native film-forming solution, the α-helix, β-turn, and random coil of the microwave-modified film-forming solution decreased by 9.2, 2, and 3%, respectively, while there was a significant increase in the β-sheet content by nearly 51%. This indicates that the protein intrinsic structure was extensively damaged by the microwave treatment (Chinnadayyala et al 2012). The effect of the microwave modification was similar to that of the heating treatment.…”
Section: Resultsmentioning
confidence: 60%
“…It is well known that microwaves induce heating by excitation of rotational motion in water molecules and that the rotational kinetic energy is then transferred to the translational degrees of freedom. The microwave irradiation is important in biology: there are reports that microwaves enhance the folding and unfolding kinetics of globular proteins [10][11][12], as well as protein aggregation [13].…”
Section: Discussionmentioning
confidence: 99%